1999
DOI: 10.1016/s0013-7944(99)00045-4
|View full text |Cite
|
Sign up to set email alerts
|

Stress intensity factors for functionally graded solid cylinders

Abstract: This paper presents the mode I stress intensity factors for functionally graded solid cylinders with an embedded penny-shaped crack or an external circumferential crack. The solid cylinders are assumed under remote uniform tension. The multiple isoparametric ®nite element method is used. Various types of functionally graded materials and dierent gradient compositions for each type are investigated. The results show that the material property distribution has a quite considerable in¯uence on the stress intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Previous applications of the DCT to 2-D models for FGMs include Li et al (1999), Marur and Tippur (2000), Rousseau and Tippur (2001) and Kim and Paulino (2002a). For an exponential material variation with E 2 =E 1 ¼ 5, Fig.…”
Section: Verification Of K I -Values For Functionally-graded Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous applications of the DCT to 2-D models for FGMs include Li et al (1999), Marur and Tippur (2000), Rousseau and Tippur (2001) and Kim and Paulino (2002a). For an exponential material variation with E 2 =E 1 ¼ 5, Fig.…”
Section: Verification Of K I -Values For Functionally-graded Specimensmentioning
confidence: 99%
“…Analytical and numerical studies of fracture in FGMs reported in the literature focus primarily on plane stress, plane strain and axisymmetric configurations (Delale and Erdogan, 1983;Eischen, 1987;Konda and Erdogan, 1994;Dag et al, 1999;Li et al, 1999;Selvadurai, 2000). As understanding of the micromechanical behavior of crack growth in FGMs progresses, computational techniques enable the analysis of realistic configurations in three-dimensions for which analytical solutions do not exist.…”
Section: Introductionmentioning
confidence: 99%
“…A cylindrical bar having an infinite row of circumferential cracks under tension loading was considered by Nisitani and Noda [17]. The mode I SIF for a functionally graded solid cylinder with an embedded penny-shaped crack or a circumferential crack is studied by Li et al [18] with the multiple isoparametric finite element method. While the SIF for a mode I crack problem in a circumferentially cracked hollow cylinder was obtained by Erdol and Erdogan [19] for the stress-free lateral surface condition, the same problem for the stress-free inner surface and rigidly fixed outer surface condition was solved by Aydin and…”
Section: Introductionmentioning
confidence: 99%
“…Notice that this subject has been already addressed in both past and present works. Specifically, previous works focused on the analysis of mode I SIF of circumferential cracks located at the outer [30] or the inner [31] wall of the cylinder; more recently, semi-elliptical circumferential surface cracks in hollow cylinders subjected to internal pressure have been also analyzed [32]; the crack opening displacements was employed to extract the mixed mode SIFs.…”
Section: Introductionmentioning
confidence: 99%